(untitled) (Research, Society and Development, 2023)
Care and attention for pregnant teenagers and the fetus begins with basic care through adequate prenatal care. From this, the Objective was constructed: To understand the strategies used to adhere pregnant teenagers to prenatal care developed by primary care nurses. Methodology: This is a narrative review research with a qualitative nature, descriptive approach. The literature review is based on bringing together authors’ approaches related to the research topic, seeking an analysis with interpretations of results. Results: The results of this analysis were carried out to respond to the objectives of the research with a survey on free access platforms, of which an initial survey of 50 publications. After analyzing the titles and abstracts, 30 publications that did not meet the proposed criteria were discarded. 20 publications were selected that were part of this theoretical contribution. Final considerations: In the studies surveyed, Nursing is related to health care and care, with nurses enabling as a strategy the use of affective communication, qualified listening, educational practice actions, welcoming consultations, the development of preventive actions and offering quality outpatient or emergency care. Therefore, with this nursing care, we see the importance of health professionals, that is, the nurse who preventively provides assistance to the mother, the baby, the partner, that is, actions that encompass the entire family with the aim of risks and complications during pregnancy are avoided, especially educational and preventive actions.